2014
DOI: 10.1097/fjc.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPAR-γ by Pioglitazone Attenuates Oxidative Stress in Aging Rat Cerebral Arteries Through Upregulating UCP2

Abstract: Increasing amounts of evidence implicate oxidative stress as having a pivotal role in age-related cerebrovascular dysfunction, which is an important risk factor for the development of cerebrovascular disease. Previous studies have shown that the activation of the expression of peroxisome proliferator-activated receptor gamma (PPAR-γ) in vascular endothelial cells results in an improvement of vascular function. Pioglitazone, a well-known PPAR-γ agonist, protects against oxidative stress in the rostral ventrolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…PPARγ, a member of PPAR superfamily, is mainly expressed in adipocytes and activates both lipogenic and lipid oxidation [ 28 ]. Reportedly, PPARγ activation attenuated ROS production in aging rat cerebral arteries and human umbilical vein endothelial cells [ 29 ]. Our previous study showed that PPARγ attenuated carotid arteries IH by inhibiting TLR4-mediated inflammation in VSMCs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPARγ, a member of PPAR superfamily, is mainly expressed in adipocytes and activates both lipogenic and lipid oxidation [ 28 ]. Reportedly, PPARγ activation attenuated ROS production in aging rat cerebral arteries and human umbilical vein endothelial cells [ 29 ]. Our previous study showed that PPARγ attenuated carotid arteries IH by inhibiting TLR4-mediated inflammation in VSMCs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chuang et al showed that activation of PPARγ by RSG enhanced UCP2 expression and further protected against oxidative stress and neuronal cell death associated with cerebral ischemia [ 38 ]. Wang et al showed that activation of PPARγ by pioglitazone attenuated oxidative stress in aging rat cerebral arteries through upregulating UCP2 [ 29 ]. However, it is still unknown whether PPARγ exerts antioxidant effect through upregulating UCP2 in PDGF-BB or wire injury induced VSMC proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise biochemical function of mitochondrial UCP2 is still a matter of debate. Accumulating literatures have showed that UCP2 plays a positive physiological role by regulating mitochondrial biogenesis, maintaining energy balance, keeping calcium homeostasis [ 11 ], ROS elimination [ 12 ], and regulating cellular autophagy [ 13 ] and, thereby, provides cellular protection and possibly anti-aging [ 14 ]. But some other studies that used inhibitors, knockdown, or mutagenesis methods indicated UCP2 might have many deleterious effects and were involved in pathogenesis of numerous diseases, such as cardiovascular diseases [ 15 ], type 2 diabetes mellitus [ 8 ], obesity [ 16 ], polycystic ovary syndrome (PCOS) [ 17 ], and various cancers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is evidence to reveal that PPAR expression is inversely correlated with inflammatory cytokines IL-1β and TNF-α in aging rats (Gelinas & Mclaurin 2005). The PPARγ agonist ameliorates aging-related renal and cerebral artery injuries by inhibiting the inflammatory genes, reducing ECM production, and attenuating oxidative stress (Sung et al 2006;Wang et al 2014;Yang et al 2009). In this study, we also found PPARγ was downregulated in the cochlear tissues of Cmah-null mice and our PPI network showed PPARG could interact with SOD2, FOS and ICAM1, implying PPARG mediated pathways may be also a considerably important mechanism for AHL and activation of PPARG may be an underlying therapeutic method for patients with AHL, which has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%